Effects of pre-steaming on the drying quality of rubberwood - Ratnasingam, Jegatheswaran; Grohmann, Rainer; Scholz, Frieder (Springer, 2014)
In this study, the kiln drying yield of 30 mm Rubberwood (Hevea brasiliensis) furniture stocks with pre-steaming treatment was evaluated. The results revealed that pre-steaming increased the permeability of the wood, hence increasing the drying rate while reducing drying defects. It was found that the pre-steaming treatment should be included in the drying of Rubberwood in order to reduce the overall drying costs as well as improving its quality.